1987
DOI: 10.1042/cs0720255
|View full text |Cite
|
Sign up to set email alerts
|

Oral absorption of the somatostatin analogue SMS 201–995: Theoretical and practical implications

Abstract: Oral administration of SMS 201-995 (SMS), a subcutaneously injectable somatostatin analogue, was investigated in five healthy volunteers, who drank 2 mg of SMS with 75 g of glucose. Mean maximal plasma SMS concentrations after the 2 mg oral dose were comparable with those after subcutaneous injection of 50 micrograms, although the peak was delayed (90 vs 15 min). Biological activity of absorbed SMS was shown by significant and lasting suppression of plasma insulin concentrations, resulting in significant hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…This octapeptide is a conformationally stabilized analog of a biologically active fragment of somatostatin in which two D amino acids were substituted in or added to the essential tetrapeptide pharmacophore: this compound is highly resistant to enzymatic degradation and is at least as active as the native hormone. In clinical trials it was found empirically by Fuessl et al (9) that oral administration of SMS 201-995 together with 75 g of glucose resulted in clinically effective plasma concentrations ofthe peptide. It is therefore reasonable to suppose that other biologically active peptides might be modified by substitution or addition of D amino acids to prevent or slow enzymatic degradation during paracellular absorption through the glucose-activated small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This octapeptide is a conformationally stabilized analog of a biologically active fragment of somatostatin in which two D amino acids were substituted in or added to the essential tetrapeptide pharmacophore: this compound is highly resistant to enzymatic degradation and is at least as active as the native hormone. In clinical trials it was found empirically by Fuessl et al (9) that oral administration of SMS 201-995 together with 75 g of glucose resulted in clinically effective plasma concentrations ofthe peptide. It is therefore reasonable to suppose that other biologically active peptides might be modified by substitution or addition of D amino acids to prevent or slow enzymatic degradation during paracellular absorption through the glucose-activated small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, there would be nothing to impede similar absorption of intact polypeptides if their hydrolysis in the brush border could be limited. Indeed, biologically active quantities of slowly degraded hormones (6) or of certain synthetic "protected" peptides (7,8) are absorbed, especially after oral administration with glucose (9). The paracellular passage of a heme-linked peptide (microperoxidase, 2000 Da) can be detected in junctional dilatations elicited by glucose (10).…”
mentioning
confidence: 99%
“…Hence, it is considered unlikely that the paracellular route is an important one for carnosine absorption; however, this could be a reflection of the relative efficiency of the brush-border transport mechanism for carnosine. It may be significant that, when Fuessl, Domin & Bloom (1987) demonstrated biological activity of an octapeptide mini-analogue of somatostatin (Sandoz SMS-201-995) after oral administration to humans, they administered it with a strongly hypertonic glucose solution (2100 mosmol/kg nominally). Hence, hypertonic solutions may enhance intestinal absorption of intact peptides, but this may be relevant only when the specificity of brush-border carriers and/or the size of the peptides denies the use of transcellular carrier-mediated mechanisms.…”
Section: L G Gardner and Othersmentioning
confidence: 99%
“…It is used clinically in the therapy of acromegaly and in the symptomatic treatment of carcinoid syndrome or endocrine tumours of the GI tract (Del Pozo, 1988;Battershill & Clissold, 1989). Recent studies in healthy volunteers have demonstrated that octreotide effectively suppresses plasma insulin levels after oral administration, indicating that functionally active peptide is absorbed (Williams et al, 1986;Fuessl et al, 1987), despite its rather low systemic bioavailability of about 0.3% (Kohler et al, 1987). It is not known, whether this low bioavailability is due to restricted absorption sites in the intestinal tract, where the drug passes by, or due to an interaction with intestinal content such as biliary or pancreatic fluids.…”
Section: Introductionmentioning
confidence: 99%